New dry lines resistant to common bacterial blight - Mohan, S. Tara; Mohan, S.K. (Pesquisa Agropecuaria Brasileira, 2014)
With the objective of incorporation of genetic resistance for common bacterial blight in commercial cultivars of bean, cultivars Carioca, Rosinha, Moruna, Rio Tibagi and Iguaçu, susceptible to the disease, were crossed with moderately resistant Great Northern Nebraska 1 sel. 27. Some of the crosses yielded segregates with levels of resistance superior to the source employed. Subsequently, these selections were intercrossed among themselves and with another blight resistant source P.I. 207-262 with the objective of accumulating and stabilizing higher levels of resistance, thus resulting in several lines with high levels of foliage resistance, in some cases accompanied by pod resistance and desirable agronomic characters.